Hydrodynamics of a tidal inlet under gray to green coastal protection interventions - Velasquez-Montoya, Liliana; Wargula, Anna; Nangle, Jessica; Sciaudone, Elizabeth; Smyre, Elizabeth; Tomiczek, Tori (Frontiers in Earth Science, 2022)
Structural coastal protection interventions have been implemented worldwide to stabilize channels and shorelines in tidal inlets. Although these conventional “gray” interventions typically attain their goals, there is an increasing interest and need to consider nature-based or “green” interventions that also address system resilience and environmental impacts. For a better implementation of gray to green interventions in tidal inlets, their effectiveness and their effects on the velocity of these dynamic coastal systems need to be understood. The effects on flow velocity of gray to green coastal protection interventions for tidal inlets are assessed here by exploring six interventions intended to protect against erosion on the estuarine-side shoreline near the inlet. A field-calibrated numerical model with Willmott Skill scores rated as excellent for Oregon Inlet located in North Carolina, United States, is used to simulate tidal currents under present conditions and after implementing a seawall, a set of bendway weirs, a terminal groin extension, a dual-jetty system, a flood channel relocation, and an island restoration project. Comparisons of time series of flow velocities in the flood channel along an eroding, estuarine shoreline are used to identify the effectiveness of each coastal protection alternative at reducing erosive velocities. Geospatial difference maps are used to determine velocity changes caused by each alternative throughout the inlet system. With no coastal protection interventions, the velocities along the eroding shoreline exceeded an erosive threshold velocity (defined as 0.2 m/s) during 50% of the simulated period. Alternatives closer to the green side of the coastal protection intervention spectrum, such as channel relocation and island restoration, tend to display the most effectiveness at reducing flow velocities at the eroding shoreline while resulting in minimal inlet-wide hydrodynamic changes. On the other hand, gray alternatives either cause minimal (seawall and bendway weirs) or extreme (jetties) changes in velocities throughout the inlet system. This comparison of gray and green coastal protection interventions in tidal inlets serves as an example to contrast the effectiveness of different coastal protection alternatives at reducing erosive flow velocities and to inform alternative selection at other inlet systems.